A Step Toward Development of Printable Dosage Forms for Poorly Soluble Drugs. Issue 10 (31st July 2013) - Raijada, Dhara; Genina, Natalja; Fors, Daniela; Wisaeus, Erik; Peltonen, Jouko; Rantanen, Jukka; Sandler, Niklas
<x xml:space="preserve">Abstract</x> The purpose of this study was to formulate printable dosage forms for a poorly soluble drug (piroxicam; PRX) and to gain understanding of critical parameters to be considered during development of such dosage forms. Liquid formulations of PRX were printed on edible paper using piezoelectric inkjet printing (PIJ) and impression printing (flexography). The printed dosage forms were characterized using scanning electron microscopy with energy dispersive X‐ray spectroscopy (SEM–EDX) and the amount of drug was determined using high‐performance liquid chromatography. Solutions of PRX in polyethylene glycol 400 (PEG‐400):ethanol (40:60) and in PEG‐400 were found to be optimal formulations for PIJ and flexography, respectively. SEM–EDX analysis revealed no visible solid particles on the printed dosage forms indicating the drug most likely remained in solution after printing. More accurate drug deposition was obtained by PIJ as compared with flexography. More than 90% drug release was achieved within 5 min regardless of printing method used. The solubility of drug in solvents/cosolvents, rheological properties of formulations, properties of substrate, feasibility and accuracy of the printing methods, and detection limit of analytical techniques for characterization of printed dosage forms are some of the concerns that need to be addressed for development of printable dosage forms of poorly soluble drugs. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:3694–3704, 2013